ERDVĖS ESTETIKOS TYRIMAS. PREKYBOS CENTRŲ ATVEJIS. - Nefaitė, Karilė (Acta Academiae Artium Vilnensis, 2012)
The object of the article's research is the aesthetics of the public spaces found in large shopping centres. The factors influencing this object, the criteria of evaluation and analysis, historical, socio-cultural and political conditions, philosophical, psychological and the assessment of the conclusions of art critics are examined. The aesthetical features and attributes of the shopping centres' public spaces are brought to the reader's attention. An aesthetics research method, based on three space image elements: meaning, structure and identity, is presented in the article. The conclusion is reached that a shopping centre is an aesthetical presentation space of economic power. The presumption that shopping centres' public spaces imitate structural models of urban public spaces is employed to examine the structure of space. Using an urban public spaces study by William H. Whyte, the main elements of urban public spaces inherent to shopping centres are revealed; their transformations and their relation with the consumerism imperative are explained. After considering the identity of shopping centres, the interior design motives used in them are revealed. The main aesthetical themes of the shopping centres are recounted. The article states that shopping centres possess the tendencies of globalisation and unification.